Response of Rice Nitrogen Physiology to High Nighttime Temperature during Vegetative Stage - Song Chen; Xiaoguo Zhang; Xia Zhao; Danying Wang; Chunmei Xu; Chenglin Ji; Xiufu Zhang (The Scientific World Journal)
The effects of night temperature on plant morphology and nitrogen accumulation were examined in rice (Oryza sativa L.) during vegetative growth. The results showed that the shoot biomass of the plants was greater at 27°C (high nighttime temperature, HNT) than at 22°C (CK). However, the increase in both shoot and root biomasses was not significant under 10 mg N/L. The shoot nitrogen concentrations were 16.1% and 16.7% higher in HNT than in CK under 160 and 40 mg N/L. These results suggest that plant N uptake was enhanced under HNT; however, the positive effect might be limited by the N status of the plants. In addition, leaf area, plant height, root maximum length, root and shoot nitrogen concentrations, soluble leaf protein content, and soluble leaf carbohydrate content were greater in HNT than in CK under 40 and 160 mg N/L, while fresh root volume, root number, and the content of free amino acid in leaf were not significantly different between HNT and CK regardless of nitrogen levels. Moreover, leaf GS activity under HNT was increased at 160 mg N/L compared with that under CK, which might partly explain the positive effect of HNT on soluble protein and carbohydrate content.